2022
DOI: 10.1177/07482337211064950
|View full text |Cite
|
Sign up to set email alerts
|

Respiratory health disorders among workers in some Egyptian welding enterprises

Abstract: Welding fumes contain a complex mixture of metallic oxides that pose a risk to welders' respiratory systems. This study aimed to evaluate respiratory health disorders among workers in some Egyptian welding enterprises and their relationship to the workplace environment. This research was performed from January 1st, 2019 to February 28th, 2021 in welding enterprises in Birket El-Sabaa, a randomly selected district of Menoufia governorate, Egypt. A cross-sectional comparative study was conducted on 110 welders a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 36 publications
0
3
0
Order By: Relevance
“…In this study, welders were exposed to higher concentrations of welding fumes than non-welders, which is consistent with the results of the environmental investigation in this study. Welders were more likely than non-welders to wear dust masks (p < 0.001) and welding face screens (p < 0.001) , and the Abdel-Rasoul study found that effective mask wearing significantly improved the respiratory function of welders ( 26 ). The intense light and ultraviolet light produced during Almahmoud welding can damage the eyes, and the welding face screen and special goggles can effectively reduce damage to the eyes ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In this study, welders were exposed to higher concentrations of welding fumes than non-welders, which is consistent with the results of the environmental investigation in this study. Welders were more likely than non-welders to wear dust masks (p < 0.001) and welding face screens (p < 0.001) , and the Abdel-Rasoul study found that effective mask wearing significantly improved the respiratory function of welders ( 26 ). The intense light and ultraviolet light produced during Almahmoud welding can damage the eyes, and the welding face screen and special goggles can effectively reduce damage to the eyes ( 27 ).…”
Section: Discussionmentioning
confidence: 99%
“…In a more recent study, Zhou S, et al demonstrated that pneumoconiosis may severely affect lung function, most commonly when working with Cr (chromium) and Zn (zinc), and it could have an impact on kidney function as they found and urinary Cd (cadmium) and also haemal Pb (plumbum/ lead). Therefore, same study have showed that even after leaving the welding environment, the lung damage would either keep the original stages or progress slowly to aggravation (12).…”
Section: Pneumoconiosismentioning
confidence: 98%
“…Multiple studies have shown that welders can develop severe chronic inflammations of the superior airway tract, most frequently described in scientific literature being chronic rhinitis (both atrophic and hyperplastic forms are mentioned in relation to welding working environment). Symptoms described associated are: anosmia (temporary or permanent), rough voice, nasal mucosa irritation and conjunctivitis (pink-eye) (4,11,12).…”
Section: Conditions Of the Upper Airways Tractmentioning
confidence: 99%